ANALISIS PEMASARAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) DI KOTA PEKANBARU - Andre Julian Pinem; Eliza Eliza; Shorea Khaswarina (Program Studi Pendidikan Ekonomi Universitas Riau, 2018)
The purpose of this research are: (1) to analyze the marketing channels; and (2) toanalyze the marketing costs, margins, profit, marketing efficiency and farmer share.The research method used survey method with 10 white oyster mushroom farmers,2 brokers, and 31 retailers. The result showed that marketing functions undertakenby institutions who involved in the marketing of white oyster mushroom includefarmers, brokers, and retailers such as exchange function, physical function, andfunction facilities. Marketing channels of white oyster mushroom in Pekanbaru cityconsists of three channels, where Channel I farmer selling white oyster mushroom toconsumer directly, Channel II farmer selling white oyster mushroom to retailer, andthen retailer selling mushroom to consumer, and Channel III farmer selling whiteoyster mushroom to broker, then broker selling mushroom to retailer, and finallyretailer selling mushroom to consumer. Total marketing cost of Channel I Rp533,00/kg, marketing margin Rp 0,00/kg, profit Rp 31.467,00/kg, marketingefficiency 1,67% and bagian farmer share100,00 %. Total marketing cost of ChannelII Rp 2.929,00per kg, marketing margin Rp 12.368,00/kg, profit Rp 8.983,00/kg,marketing efficiency 7,32% and bagian farmer share69,08%. Total marketing cost ofChannel III Rp 3.291,00/kg, marketing margin Rp 13.000,00/kg, profit Rp9.709,00/kg, marketing efficiency 7,84% and bagian farmer share69,05%.